American Society of Clinical Oncology/College of American Pathologists 2018 Focused Update of Breast Cancer HER2 FISH Testing GuidelinesResults From a National Reference Laboratory. Issue 4 (7th June 2019) - Lin, Leo; Sirohi, Deepika; Coleman, Joshua F; Gulbahce, H Evin
Abstract: Objectives: To review impact of the ASCO/CAP 2018 update on HER2 testing. Methods: HER2 fluorescence in situ hybridization (FISH) test requests from primary and metastatic breast cancers between August 2018 and January 2019 were included. FISH results requiring a changed algorithm under the new guidelines (groups 2, 3, and 4) were identified and HER2:CEN17 ratios, average HER2, CEN17 signals/cell, and HER2 immunohistochemistry (IHC) results were recorded. Results: Of the HER2 FISH cases 176/812(21.7%) fell within groups 2, 3, or 4; 0/12, 1/12, and 2/152 cases were positive (3+) by IHC, and 1/12, 2/12, and 6/152 cases were positive after targeted scoring from groups 2, 3, and 4, respectively. Following 2018 updates, 8.3%, 25%, and 5.3% of the groups 2, 3, and 4 were positive, respectively. Conclusions: Groups 2, 3, and 4 constituted over 20% of HER2 FISH tests in a reference laboratory. The 2018 ASCO/CAP update significantly decreased the HER2 positivity rate.